Tubeufia sahyadriensis (Tubeufiaceae), a new dictyosporous anamorph from the Western Ghats, India - Rajeshkumar, Kunhiraman C.; Hyde, Kevin D.; Wijayawardene, Nalin N.; Madrid, Hugo; Lad, Sneha S.; Boonmee, Saranyaphat; Fatima, Shahnoor (Phytotaxa, 2019)
An unusual anamorphic dictyosporous species, Tubeufia sahyadriensis, was collected on decaying Bambusa bambos litter in the Tamhini Ghats in the northern Western Ghats of Maharashtra, India. This new species can be easily differentiated from allied Tubeufia species by its dark brownish to umber, maize corncob-like dictyoseptate conidia with reduced, simple cylindrical conidiogenous cells. Phylogenetic analyses using ITS, LSU and TEF1α sequence data delineated the new species within the genus Tubeufia under family Tubeufiaceae.